Perlindungan Data Pribadi Serta Faktor-Faktor Penghambat Penyidikan Tindak Pidana Penyalahgunaan Data Pribadi Studi di Direskrimsus Polda Lampung - Shafira, Maya; Susanti, Emilia; Amabel, Xenia Riama (VIVA THEMIS, 2023)
The object of discussion in this study is the form of personal data protection and the factors that hinder investigations into criminal acts of misuse of personal data. This research aims to determine the form of protection of people's personal data and the obstacles in the process of investigating misuse of personal data. This research method uses a normative juridical approach because it examines legal aspects and legal rules using literature material. The research specifications use descriptive analysis laws. The research results show that forms of personal data protection in Indonesia exist and are regulated in Law Number 27 of 2022 concerning Personal Data Protection, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, as well as Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions. The inhibiting factors for the Lampung Regional Police's Ditreskrimsus in carrying out investigations into misuse of personal data include legal instrument factors, apparatus factors, facilities and infrastructure factors, community factors and cultural factors.